The influence of exposure to UVβ of fluorescent light on the bone remodeling of hypoestrogenic Macaca fascicularis (Medical Journal of Indonesia, 2001)
The prevention of osteoporosis is a spesific problem that should be dealt with by increasing the women's lift expectation. The decrease of calcitriol and estrogen levels, which have a receptor in the osteoblast, will result in bone mineralization (due to calcitriol) and the information of type 1 collagen (due to estrogen). The formation of calcitriol with the main basic materials from vitamin D3 is achieved with the aid of sunray UVβ, The changes in the lifestyle of women, which make them now accustomed to performing indoor activities and prevent them from being exposed to UVβ all day, have resulted in the decrease of vitamin D3 in calcitriol in women. In addition, when entering the menopausal age they will be threatened with early osteoporosis. The exposure to the UVβ of fluorescent light with the wave length identical to sun of 290-320 nm has long been known as a modality for treating skin diseases in the hope that the production of vitamin D3 will be increased. We exposed Macaca fascicularis, whose estrogen levels were set at normal, beginning low, beginning very low levels, to UVβ of fluorescent light. It showed that the Macaca fascicularis that were exposed to UVβ experienced an increase in osteocalcin with unchanged DPD which means that bone remodeling remains unchanged. By contrast, Macaca fascicularis with normal, beginning low, and beginning very low estrogen levels which were not exposed to UVÎ² were found to experience a decrease in osteocalcin and unchanged DPD levels. This means that a change has occurred in the bone remodeling toward bone resorption.